2004
DOI: 10.1097/01.ju.0000100385.93801.d4
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Capsaicin Versus Resiniferatoxin for the Treatment of Detrusor Hyperreflexia in Spinal Cord Injured Patients:: A Double-Blind, Randomized, Controlled Study

Abstract: Our results strongly argue for the importance of accounting for the role of vanilloid solute when interpreting the efficacy and tolerance of vesical vanilloid instillation in detrusor hyperreflexia cases. They suggest that a glucidic solute is a valuable solvent for vanilloid instillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
17

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 19 publications
3
58
0
17
Order By: Relevance
“…In a recent capsaicin versus resiniferatoxin (RTX) controlled study, we reported that glucidic capsaicin was as e⁄-cient and safe as 10% ethanol RTX on NDO in 39 SCI patients [de Se' ze et al, 2004]. The present multicenter study, which includes several neurourological centers which are not particularly involved in vanilloid development, strengthened the demonstration of the feasibility and validity of this treatment procedure.…”
Section: Discussionsupporting
confidence: 63%
“…In a recent capsaicin versus resiniferatoxin (RTX) controlled study, we reported that glucidic capsaicin was as e⁄-cient and safe as 10% ethanol RTX on NDO in 39 SCI patients [de Se' ze et al, 2004]. The present multicenter study, which includes several neurourological centers which are not particularly involved in vanilloid development, strengthened the demonstration of the feasibility and validity of this treatment procedure.…”
Section: Discussionsupporting
confidence: 63%
“…14 Intravesical administration of capsaicin or resiniferatoxin might result in unwanted side effects such as suprapubic burning sensation, hematuria, urine leakage, a hot flush, and/or signs of AD. 15 BoNT-A injection into bladder detrusor muscle could use but it is expansive and it need the another procedure, cystoscopy. And sacral rhizotomy could also be used, but these methods are invasive and could incur complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RTX did not evoke the same irritating side effects as capsaicin. 98 de Sèze et al 99 however, did not observe any differences in efficacy and tolerance between capsaicin dissolved in glucidic solvent and RTX dissolved in 10% ethanol. They suggest that differences between the effect of capsaicin and RTX in previous studies are strongly influenced by the vanilloid solute.…”
Section: Trpv1 As Therapeutic Targetmentioning
confidence: 91%